Modified silicon particles for silicon-carbon composite electrodes
Patent Information
- Application Number
- KR1020217042973
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-06-03
- Filing Date
- 2020-06-03
- Publication Date
- 2026-09-15
- Estimated Expiration
- 2040-06-03
Smart Images

Figure 112021151840961-PCT00009_ABST
Abstract
Description
Technology Field
[0001] This application generally relates to silicon particles. More specifically, this application relates to silicon particles for use in battery electrodes and composite materials comprising silicon particles. Background Technology
[0002] Lithium-ion batteries generally include a separator and / or electrolyte between the anode and cathode. In one class of batteries, the separator, cathode, and anode materials are formed individually as sheets or films. Subsequently, the sheets of the cathode, separator, and anode are stacked or rolled to form a battery, with a separator separating the cathode and anode (e.g., electrodes). Typical electrodes include a layer of electrochemical active material on an electrically conductive metal (e.g., aluminum and copper). The film can be rolled or cut into pieces and then stacked. The stack consists of alternating electrochemical active materials with a separator in the middle.
[0003] In a specific embodiment, a method for forming a composite film is disclosed. The method may include the step of providing a mixture comprising a precursor and silane-treated silicon particles. The method may further include the step of pyrolyzing the mixture to convert the precursor into one or more carbon phases to form a composite film having silicon particles distributed across the composite film.
[0004] In various embodiments, the silane-treated silicon particles may comprise silicon particles treated with one or more organosilanes. For example, the silane-treated silicon particles may comprise a silicon oxide surface that reacts with the one or more organosilanes. In some cases, the one or more organosilanes may comprise one or more silanols, silyl ethers, silyl chlorides, dialkylaminosilanes, silyl hydrides, or cyclic azasilanes.
[0005] In some methods, one or more organosilanes may comprise one or more aminoalkyl functional groups. For example, one or more organosilanes may comprise 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, or 2,2-dimethoxy-1,6-diaza-2-silacyclooctane. In some cases, the precursor may comprise a polyimide.
[0006] In some methods, one or more organosilanes may comprise an epoxide linker. For example, the epoxide linker may comprise 5,6-epoxyhexyltriethoxysilane. In some cases, the precursor may comprise a phenol resin.
[0007] In some methods, one or more organosilanes may include aromatic functional groups. For example, one or more organosilanes may include benzyltriethoxysilane. In some cases, the precursor may include a polycyclic aromatic hydrocarbon.
[0008] In some methods, one or more organosilanes may include dodecylsilanes.
[0009] In some methods, one or more organosilanes may include (N,N-dimethylamino)trimethylsilane.
[0010] In some methods, the silicon particles may be suspended in a liquid containing one or more organosilanes.
[0011] In some methods, the silicon particles may be exposed to one or more organosilane vapors.
[0012] In some methods, the mixture may include one or more organosilanes.
[0013] In some embodiments, the composite film may comprise about 50 weight percent to about 99 weight percent of silicon particles. The composite film may be electrochemically active. One or more types of carbon phases may be a continuous phase that maintains the composite film.
[0014] In various embodiments, a method for forming a battery electrode is disclosed. The electrode may comprise a composite material film as described herein. In some cases, the electrode may be an anode. Brief explanation of the drawing
[0015] FIG. 1a illustrates an embodiment of a method for forming a composite material, comprising the steps of forming a mixture containing a precursor, casting the mixture, drying the mixture, curing the mixture, and pyrolyzing the precursor. Figure 1b is a schematic diagram of forming silicon carbide on silicon particles. FIGS. 2a and 2b are SEM microscope images of one embodiment of micron-sized silicon particles milled-down from larger silicon particles. FIGS. 2C and 2D are SEM microscope images of one embodiment of micron-sized silicon particles having nanometer-sized features on their surface. FIG. 2e illustrates an exemplary embodiment of a method for forming a composite material. FIG. 3a schematically illustrates exemplary silane-treated silicon particles. FIG. 3b illustrates an exemplary embodiment of a method for forming a composite material. Figure 4 is a plot of the discharge capacity at an average rate of C / 2.6. Figure 5 is a plot of the discharge capacity at an average ratio of C / 3. Figure 6 is a plot of the discharge capacity at an average ratio of C / 3.3. Figure 7 is a plot of the discharge capacity at an average ratio of C / 5. Figure 8 is a plot of the discharge capacity at an average ratio of C / 9. Figure 9 is a plot of discharge capacity. Figure 10 is a plot of the discharge capacity at an average ratio of C / 9. FIGS. 11a and 11b are plots of reversible and irreversible capacities as a function of various weight percentages of PI-derived carbon and graphite particles of 2611c for a fixed percentage of 20 wt% Si. Figure 12 is a plot of the first cycle discharge capacity as a function of the weight percentage of carbon. Figure 13 is a plot of reversible (discharge) and irreversible capacities as a function of pyrolysis temperature. Figure 14 is a photograph of a 4.3 cm × 4.3 cm composite anode membrane without a metal foil support layer. Figure 15 is a scanning electron microscope (SEM) image of a composite anode membrane before cycling (the out-of-focus area is the bottom of the anode, and the in-focus area is the cleaved edge of the composite membrane). Figure 16 is another SEM micrograph of the composite anode membrane before cycling. Figure 17 is an SEM micrograph of the composite anode membrane after 10 cycles. Figure 18 is another SEM micrograph of the composite anode membrane after cycling 10 cycles. Figure 19 is an SEM micrograph of the composite anode membrane after 300 cycles. Figure 20 includes an SEM microscope image of a cross- section of a composite anode membrane. Figure 21 is an X-ray powder diffraction (XRD) graph of sample silicon particles. Figure 22 is an SEM microscope image of one embodiment of silicon particles. Figure 23 is another SEM microscope image of one embodiment of silicon particles. Figure 24 is an SEM microscope image of one embodiment of silicon particles. Figure 25 is an SEM microscope image of one embodiment of silicon particles. Figure 26 is a chemical analysis of the sample silicon particles. FIGS. 27a and FIGS. 27b are histograms of exemplary particle sizes of two micron-sized silicon particles having nanometer-sized features. Figure 28 is a plot of discharge capacity during cell cycling comparing two types of exemplary silicon particles. FIG. 29 shows the X-ray photoelectron spectroscopy (XPS) spectra for exemplary silane-treated silicon particles and untreated silicon particles. FIG. 30a is a focused ion beam (SEM-FIB) scanning electron microscope image of a cross- section of an exemplary silicon-carbon composite material made from untreated silicon particles. Figure 30b is an SEM-FIB microscope image of a cross- section of an exemplary silicon-carbon composite material prepared from silane-treated silicon particles. Figure 31 shows a graph of capacity retention versus cycle count for a whole cell containing silane-treated silicon particles versus a whole cell containing untreated silicon particles. Figure 32 shows a graph of capacity retention versus number of cycles for a whole cell containing silane-treated silicon particles versus a whole cell containing untreated silicon particles in a subsequent attempt. Specific details for implementing the invention
[0016] Silicon-carbon composite electrodes may comprise silicon particles suspended in a carbon matrix. The electrode may comprise a composite material attached to a current collector or as a self-supporting structure. Silicon-carbon electrodes can provide superior energy density compared to industry-standard graphite electrodes. Silicon-carbon electrodes can also have superior cycle life and initial Coulomb efficiency compared to silicon electrodes composed of silicon particles, conductive additives, and polymer binders.
[0017] In some embodiments for manufacturing silicon composite electrodes, silicon particles may be suspended in an organic thermoplastic or thermosetting binder to form a self-supporting film, which may be heat-treated to convert the organic material into carbon. The carbon matrix may serve as an electrically conductive structural component capable of holding the electrodes together. In some of these designs, it may be advantageous for the carbon to be in close contact with the silicon particles. To achieve this close contact, the silicon particles may be wetted by a carbon precursor (e.g., substantially wetted or, in some cases, completely wetted) (e.g., to achieve increased and / or maximum interfacial contact), and it may be advantageous for the precursor to adhere strongly to the silicon particles. Without being bound by theory, if the silicon particles are not wetted by the carbon precursor, voids and / or porosity may appear at the interface between the silicon and carbon, which may have a negative effect on the strength and conductivity of the composite.
[0018] As described in this specification, in some embodiments, using silicon particles with customized surface chemical properties can improve wettability by matching surface energy with a carbon precursor, and can promote strong adhesion by providing reactive sites on the surface of the silicon particles to enable one or more bonding interactions with the carbon precursor, such as pi-stacks, dipole-dipole interactions, hydrogen bonds, and / or covalent bonds.
[0019] Conventional carbon anode electrodes include a current collector, such as a copper sheet. Carbon is deposited on the current collector along with an inert binder material. Carbon is frequently used because it possesses excellent electrochemical properties and electrical conductivity. If the current collector layer (e.g., a copper layer) is removed, the carbon may not be mechanically self-supporting. Therefore, conventional electrodes require a supporting structure, such as a current collector, to function as an electrode. The electrode compositions (e.g., anode or cathode) described herein can produce self-supporting electrodes. Since conductive carbon polymers are used to collect current and provide mechanical support in the anode structure, metal foil current collectors are not required or are minimized. In typical applications in the mobile industry, metal current collectors are generally added to ensure sufficient rate performance. Unlike one class of conventional lithium-ion battery electrodes where particulate carbon is suspended in a non-conductive binder, carbon polymers can form a substantially continuous conductive carbon phase across the entire electrode. The advantages of carbon composite blends utilizing carbon polymers may include, for example, 1) higher capacity, 2) improved overcharge / discharge protection, 3) lower irreversible capacity due to the removal (or minimization) of metal foil current collectors, and 4) potential cost reductions due to simpler manufacturing.
[0020] The anode electrodes currently used in rechargeable lithium-ion cells generally have a specific capacity of approximately 200 milliampere-hours per gram (composed of metal foil current collectors, conductive additives, and binder materials). Graphite, the active material used in most lithium-ion battery anodes, has a theoretical energy density of 372 milliampere-hours / gram (mAh / g). In comparison, silicon has a higher theoretical capacity of 4,200 mAh / g. Silicon can be used as an active material for the cathode or anode to increase the volumetric and gravimetric energy densities of lithium-ion batteries. Additionally, various types of silicon materials, such as silicon nanopowder, silicon nanowires, porous silicon, and ball-milled silicon, have been reported as viable candidates for active materials for negative or positive electrodes. Small particle sizes (e.g., in the nanometer range) can generally increase cycle life performance. They can also exhibit very high irreversible capacity. However, small particle sizes can also result in very low volumetric energy density (e.g., for the entire cell stack) due to the difficulty of packing the active material. Larger particle sizes (e.g., in the micrometer or micron range) can generally produce anode materials with higher density. However, the expansion of silicon active material can lead to reduced cycle life due to particle cracking. For example, silicon can expand by more than 300% upon lithium insertion. Due to this expansion, silicon-containing anodes must be allowed to expand while maintaining electrical contact between the silicon particles.
[0021] As described in this specification and in U.S. Patent Application No. 13 / 008,800 (U.S. Patent No. 9,178,208) (Title of invention: "Composite Materials for Electrochemical Storage") and U.S. Patent Application No. 13 / 601,976 (U.S. Patent Application Publication No. 2014 / 0170498) (Title of invention: "Silicon Particles for Battery Electrodes") (these documents are incorporated herein by reference in their entirety), certain embodiments utilize a method for creating monolithic, self-supporting anodes using a carbonized polymer. Because the polymer is converted into an electrically conductive and electrochemically active matrix, the resulting electrode is sufficiently conductive to allow the omission or minimization of metal foil or mesh current collectors. The converted polymer also acts as an expansion buffer for silicon particles during cycling, enabling high cycle life to be achieved. In certain embodiments, the resulting electrode is substantially composed of active material. In additional embodiments, the resulting electrode is substantially active material. The electrode may have a high energy density of about 500 mAh / g to about 3500 mAh / g, which may be due to, for example, 1) the use of silicon, 2) the removal or significant reduction of the metal current collector, and 3) the entire or substantially entire composition of the active material.
[0022] As described in U.S. Patent Application No. 14 / 821,586 (U.S. Patent Application Publication No. 2017 / 0040598) (Title of the invention, "Surface Modification of Silicon Particles for Electrochemical Storage") (the entire contents of which are incorporated herein by reference), in certain embodiments, a carbonized polymer may react with a natural silicon oxide surface layer on silicon particles. In some embodiments, the surface of the particles is modified to form a surface coating thereon, which may additionally serve as an expansion buffer for the silicon particles during cycling. The surface coating may comprise silicon carbide.
[0023] The composite materials described herein may be used as anodes in most conventional lithium-ion batteries; they may also be used as cathodes in some electrochemical couples with additional additives. The composite materials may also be used in secondary batteries (e.g., rechargeable batteries) or primary batteries (e.g., non-rechargeable batteries). In certain embodiments, the composite materials are self-supporting structures. In further embodiments, the composite materials are self-supporting monolithic structures. For example, an electrode made of the composite material may include a current collector. In certain embodiments, the composite materials may be used to form carbon structures discussed in U.S. Patent Application No. 12 / 838,368 (U.S. Patent Application Publication No. 2011 / 0020701) (Title of Invention: "Carbon Electrode Structures for Batteries") (the entire contents of which are incorporated herein by reference). Additionally, the composite materials described herein may be, for example, silicon composites, carbon composites, and / or silicon-carbon composites. As described in U.S. Patent Application No. 13 / 799,405 (U.S. Patent No. 9,553,303) (Title of Invention: “Silicon Particles for Battery Electrodes”) (the entire contents of which are incorporated herein by reference), certain embodiments may further comprise a composite material comprising micron-sized silicon particles. For example, in some embodiments, the micron-sized silicon particles have nanometer-sized features on their surface. Silicon particles having such a geometry may have the advantages of both micron-sized silicon particles (e.g., high energy density) and nanometer-sized silicon particles (e.g., good cycling behavior). As used herein, the term “silicon particles” may generally include micron-sized silicon particles with or without nanometer-sized features.
[0024] Some composite materials may be provided on the current collector. In some embodiments, the composite material may be attached to the current collector using an adhesive material. The adhesive material and the current collector may be any known in the art or not yet developed. For example, some composite materials may be provided on the current collector as described in U.S. Patent Application No. 13 / 333,864 (U.S. Patent No. 9,397,338) (Title of invention: "Electrodes, Electrochemical Cells, and Methods of Forming Electrodes and Electrochemical Cells") or U.S. Patent Application No. 13 / 796,922 (U.S. Patent No. 9,583,757) (Title of invention: "Electrodes, Electrochemical Cells, and Methods of Forming Electrodes and Electrochemical Cells") (each of these documents is incorporated herein by reference in its entirety). Some anodes may be formed on a current collector, for example, as described in U.S. Patent Application No. 15 / 471,860 (U.S. Patent Application Publication No. 2018 / 0287129) (Title of invention: "Methods of Forming Carbon-Silicon Composite Material on a Current Collector") (the entire contents of which are incorporated herein by reference).
[0025] FIG. 1a illustrates one embodiment of a method for forming a composite material (100). For example, the method for forming the composite material may include the step of forming a mixture containing a precursor (block (101)). The method may further include the step of pyrolyzing the precursor to convert the precursor into a carbon phase. The precursor mixture may include a carbon additive such as a graphite active material, cut or milled carbon fibers, carbon nanofibers, carbon nanotubes, and / or other carbon. After pyrolyzing the precursor, the resulting carbon material may be a self-supporting monolithic structure. In certain embodiments, one or more materials are added to the mixture to form the composite material. For example, silicon particles may be added to the mixture. The carbonization precursor creates an electrochemically active structure that holds the composite material together. For example, the carbonization precursor may be substantially a continuous phase. Silicon particles, including micron-sized silicon particles with or without nanometer-sized features, may be distributed throughout the composite material. Advantageously, the carbonization precursor may be a structural material as well as an electrochemically active and electrically conductive material. In certain embodiments, material particles added to the mixture are distributed homogeneously or substantially homogeneously across the composite material to form a homogeneous or substantially homogeneous composite material.
[0026] The mixture may contain various different components. The mixture may contain one or more precursors. In certain embodiments, the precursor is a hydrocarbon compound. For example, the precursor may include polyamideimide, polyamic acid, polyimide, etc. Other precursors may include phenolic resin, epoxy resin, and / or other polymers. The mixture may further contain a solvent. For example, the solvent may be N-methyl-pyrrolidone (NMP). Other possible solvents include acetone, diethyl ether, gamma-butyrolactone, isopropanol, dimethyl carbonate, ethyl carbonate, dimethoxyethane, ethanol, methanol, etc. Examples of precursor and solvent solutions include PI-2611 (HD Microsystems), PI-5878G (HD Microsystems), and VTEC PI-1388 (RBI, Inc.). PI-2611 consists of more than 60% n-methyl-2-pyrrolidone and 10-30% s-biphenyl dianhydride / p-phenylenediamine. PI-5878G consists of more than 60% n-methylpyrrolidone, 10 to 30% polyamic acid of pyromellitic acid dianhydride / oxydianiline, and 10 to 30% aromatic hydrocarbons (petroleum distillates) including 5 to 10% 1,2,4-trimethylbenzene. In certain embodiments, the amount of precursor in the solvent is about 10% by weight to about 30% by weight. Additional materials may be included in the mixture. For example, as previously discussed, silicon particles or carbon particles including graphite active material, cut or milled carbon fibers, carbon nanofibers, carbon nanotubes, graphene, and other conductive carbon may be added to the mixture. In addition, the mixture can be homogenized by mixing it.
[0027] In certain embodiments, the mixture is cast onto a substrate in block (102) of FIG. 1a. In some embodiments, the casting involves using gap extrusion, tape casting, or blade casting techniques. Blade casting techniques may involve applying a coating to the substrate using a flat surface (e.g., a blade) controlled at a specific distance over the substrate. A liquid or slurry may be applied to the substrate, and the liquid may be diffused over the substrate by passing the blade over the liquid. The thickness of the coating may be controlled by the gap between the blade and the substrate as the liquid passes through the gap. Excess liquid may also be scraped off as the liquid passes through the gap. For example, the mixture may be cast onto a substrate comprising a polymer sheet, a polymer roll, and / or a foil or roll made of glass or metal. The mixture may then be dried to remove the solvent (block (103)). For example, the polyamic acid and NMP solution may be dried at about 110°C for about 2 hours to remove the NMP solution. The dried mixture can then be removed from the substrate. For example, the aluminum substrate can be etched with HCl. Alternatively, the dried mixture can be removed from the substrate by peeling the dried mixture off or mechanically removing it. In some embodiments, the substrate is, for example, Mylar It comprises polyethylene terephthalate (PET) containing [the component]. In certain embodiments, the dried mixture is a membrane or a sheet. In some embodiments, the dried mixture is optionally cured (block (104)). In some embodiments, the dried mixture may be further dried. For example, the dried mixture may be placed in a hot press (e.g., between graphite plates in an oven). The hot press may be used to perform further drying and / or curing and to keep the dried mixture flat. For example, the dried mixture from the polyamic acid and NMP solution may be hot-pressed at about 200°C for about 8 to about 16 hours. Alternatively, the entire process, including casting and drying, may be performed as a roll-to-roll process using standard membrane processing equipment. The dried mixture may be rinsed to remove any remaining solvent or etchant. For example, the dried mixture may be rinsed using deionized water (DI water). In certain embodiments, tape casting technology may be used for casting. In some embodiments, the mixture may be coated onto a substrate by a slot die coating process (e.g., by weighing a constant or substantially constant weight and / or volume through a set or substantially set gap). In some other embodiments, there is no substrate to cast, and the anode film does not need to be removed from any substrate. The dried mixture may be cut or mechanically divided into smaller pieces.
[0028] Additionally, the mixture is pyrolyzed to convert the polymer precursor into carbon (block (105)). In certain embodiments, the mixture is pyrolyzed in a reducing atmosphere. For example, an inert atmosphere, vacuum, and / or flowing argon, nitrogen, or helium gas may be used. In some embodiments, the mixture is heated to about 900°C to about 1350°C. For example, a polyimide formed from polyamic acid may be carbonized at about 1175°C for about 1 hour. In certain embodiments, the heating and / or cooling rate of the mixture is about 10°C / min. A holder may be used to maintain the mixture in a specific shape. The holder may be graphite, metal, etc. In certain embodiments, the mixture is kept flat. After the mixture is pyrolyzed, a tab may be attached to the pyrolyzed material to form an electrical contact. For example, nickel, copper, or an alloy thereof may be used for the tab.
[0029] In certain embodiments, one or more of the methods described herein may be performed as a continuous process. In certain embodiments, casting, drying, possibly curing, and pyrolysis may be performed as a continuous process. For example, the mixture may be coated onto a glass or metal cylinder. The mixture may be dried while rotating in the cylinder to form a film. For further processing, the film may be transferred to a roll or peeled off and fed to another machine. Extrusion and other film manufacturing techniques known in the industry may also be used prior to the pyrolysis step.
[0030] When the precursor is pyrolyzed, a carbon material (e.g., at least one carbon phase) is produced. In certain embodiments, the carbon material is hard carbon. In some embodiments, the precursor is any material capable of being pyrolyzed to form hard carbon. If the mixture comprises one or more additional materials or phases in addition to the carbonization precursor, a composite material may be produced. In particular, the mixture may comprise silicon particles that produce a silicon-carbon (e.g., at least one first phase comprising silicon and at least one second phase comprising carbon) or silicon-carbon-carbon (e.g., at least one first phase comprising silicon, at least one second phase comprising carbon, and at least one third phase comprising carbon) composite material.
[0031] Silicon particles can increase the lithium insertion capacity of composite materials. When silicon absorbs lithium ions, its volume increases significantly by more than 300%, which can cause integrity issues in the electrode structure. In addition to problems related to volume expansion, silicon is inherently non-electrically conductive but becomes conductive when alloyed with lithium (e.g., lithiation). When silicon is delithiated, the silicon surface loses electrical conductivity. Furthermore, delithiation causes a decrease in volume, potentially leading to silicon particles losing contact with the matrix. This rapid change in volume also causes mechanical failure in the silicon particle structure, resulting in structural fragmentation. Due to fragmentation and the loss of electrical contact, using silicon as an active material in lithium-ion batteries has become difficult. Reducing the initial size of silicon particles can not only prevent further fragmentation of the silicon powder but also minimize the loss of surface electrical conductivity. Additionally, adding materials to the composite that can elastically deform in response to volume changes of the silicon particles can reduce the likelihood of electrical contact loss with the silicon surface. For example, the composite material may contain carbon, such as graphite, which can insert lithium ions (e.g., chemically active) that contribute to the composite's ability to absorb expansion and add to the electrode's storage capacity. Thus, the composite material may contain one or more types of carbon phases.
[0032] In some embodiments, the particle size (e.g., diameter or maximum dimension of the silicon particle) may be less than about 50 µm, less than about 40 µm, less than about 30 µm, less than about 20 µm, less than about 10 µm, less than about 1 µm, about 10 nm to about 50 µm, about 10 nm to about 40 µm, about 10 nm to about 30 µm, about 10 nm to about 20 µm, about 0.1 µm to about 20 µm, about 0.5 µm to about 20 µm, about 1 µm to about 20 µm, about 1 µm to about 15 µm, about 1 µm to about 10 µm, about 10 nm to about 10 µm, about 10 nm to about 1 µm, less than about 500 nm, less than about 100 nm, about 100 nm, etc. All, substantially all, or at least part of the silicon particle may comprise the aforementioned particle size (e.g., diameter or maximum dimension). For example, the average particle size (or average diameter or average maximum dimension) or median particle size (or median diameter or median maximum dimension) of the silicon particles may be less than about 50 µm, less than about 40 µm, less than about 30 µm, less than about 20 µm, less than about 10 µm, less than about 1 µm, about 10 nm to about 50 µm, about 10 nm to about 40 µm, about 10 nm to about 30 µm, about 10 nm to about 20 µm, about 0.1 µm to about 20 µm, about 0.5 µm to about 20 µm, about 1 µm to about 20 µm, about 1 µm to about 15 µm, about 1 µm to about 10 µm, about 10 nm to about 10 µm, about 10 nm to about 1 µm, less than about 500 nm, less than about 100 nm, about 100 nm, etc. In some embodiments, the silicon particles may have a distribution of particle sizes. For example, at least about 95%, at least about 90%, at least about 85%, at least about 80%, at least about 70%, or at least about 60% of the particles may have the particle size described herein.
[0033] The amount of silicon provided to the mixture or composite material may be greater than 0 weight percent of the mixture and / or composite material. In certain embodiments, the amount of silicon may be in the range of about 0 wt% to about 99 wt% of the composite material, greater than about 0 wt% to about 99 wt%, greater than about 0 wt% to about 95 wt%, greater than about 0 wt% to about 90 wt%, greater than about 0 wt% to about 35 wt%, greater than about 0 wt% to about 25 wt%, about 10 wt% to about 35 wt%, at least about 30 wt%, about 30 wt% to about 99 wt%, about 30 wt% to about 95 wt%, about 30 wt% to about 90 wt%, about 30 wt% to about 80 wt%, at least about 50 wt%, about 50 wt% to about 99 wt%, about 50 wt% to about 95 wt%, about 50 wt% to about 90 wt%, about 50 wt% to about 80 wt%, about 50 wt%. It may be within a range including to about 70 weight%, at least about 60 weight%, about 60 weight% to about 99 weight%, about 60 weight% to about 95 weight%, about 60 weight% to about 90 weight%, about 60 weight% to about 80 weight%, at least about 70 weight%, about 70 weight% to about 99 weight%, about 70 weight% to about 95 weight%, about 70 weight% to about 90 weight%, etc.
[0034] Additionally, the silicon particles may or may not be pure silicon. For example, the silicon particles may be substantially silicon or may be a silicon alloy. In one embodiment, the silicon alloy comprises silicon as a major component along with one or more other elements.
[0035] The micron-sized silicon particles described herein can provide good volumetric and gravimetric energy densities combined with good cycle life. In certain embodiments, to obtain the benefits of both micron-sized silicon particles (e.g., high energy density) and nanometer-sized silicon particles (e.g., good cycle behavior), the silicon particles may have a surface comprising an average particle size or intermediate particle size in the micron range and nanometer-sized features. In some embodiments, the silicon particles may have an average particle size (e.g., average diameter or average maximum dimension) or intermediate particle size (e.g., intermediate diameter or intermediate maximum diameter) of any value from about 0.1 µm to about 30 µm or from about 0.1 µm to a maximum of about 30 µm. For example, silicon particles may have an average particle size or an intermediate particle size such as about 0.1 µm to about 20 µm, about 0.5 µm to about 25 µm, about 0.5 µm to about 20 µm, about 0.5 µm to about 15 µm, about 0.5 µm to about 10 µm, about 0.5 µm to about 5 µm, about 0.5 µm to about 2 µm, about 1 µm to about 20 µm, about 1 µm to about 15 µm, about 1 µm to about 10 µm, about 5 µm to about 20 µm, etc. Accordingly, the average particle size or the intermediate particle size may be any value from about 0.1 µm to about 30 µm, and for example, may be 0.1 µm, 0.5 µm, 1 µm, 5 µm, 6 µm, 7 µm, 8 µm, 9 µm, 10 µm, 15 µm, 20 µm, 25 µm, and 30 µm.
[0036] The nanometer-sized feature may include an average feature size (e.g., average diameter or average maximum dimension) of about 1 nm to about 1 µm, about 1 nm to about 750 nm, about 1 nm to about 500 nm, about 1 nm to about 250 nm, about 1 nm to about 100 nm, about 10 nm to about 500 nm, about 10 nm to about 250 nm, about 10 nm to about 100 nm, about 10 nm to about 75 nm, or about 10 nm to about 50 nm. The feature may include silicon.
[0037] The amount of carbon obtained from the precursor can be about 50 weight percent from the polyamic acid. In certain embodiments, the amount of carbon obtained from the precursor of the composite material may be greater than 0 wt% to about 95 wt%, for example, about 1 wt% to about 95 wt%, about 1 wt% to about 90 wt%, 1 wt% to about 80 wt%, about 1 wt% to about 70 wt%, about 1 wt% to about 60 wt%, about 1 wt% to about 50 wt%, about 1 wt% to about 40 wt%, about 1 wt% to about 30 wt%, about 5 wt% to about 95 wt%, about 5 wt% to about 90 wt%, about 5 wt% to about 80 wt%, about 5 wt% to about 70 wt%, about 5 wt% to about 60 wt%, about 5 wt% to about 50 wt%, about 5 wt% to about 40 wt%, about 5 wt% to about 30 wt%, about 10 The amount may be in the range of weight% to about 95 weight%, about 10 weight% to about 90 weight%, about 10 weight% to about 80 weight%, about 10 weight% to about 70 weight%, about 10 weight% to about 60 weight%, about 10 weight% to about 50 weight%, about 10 weight% to about 40 weight%, about 10 weight% to about 30 weight%, about 10 weight% to about 25 weight%, etc. For example, the amount of carbon obtained from the precursor may be about 1 weight%, about 5 weight%, about 10 weight%, about 15 weight%, about 20 weight%, about 25 weight%, etc.
[0038] The carbon from the precursor may be hard carbon. Hard carbon may be carbon that does not convert into graphite even when heated to temperatures exceeding 2800 degrees Celsius. The precursor that melts or flows during pyrolysis converts into soft carbon and / or graphite at sufficient temperature and / or pressure. Hard carbon may be selected because the soft carbon precursor can flow and soft carbon and graphite are mechanically weaker than hard carbon. Other possible hard carbon precursors may include phenolic resin, epoxy resin, and other polymers that have very high melting points or are cross-linked. In some embodiments, the amount of hard carbon in the composite material may have a value within the range of greater than 0 wt% to about 95 wt%, for example, about 1 wt% to about 95 wt%, about 1 wt% to about 90 wt%, about 1 wt% to about 80 wt%, about 1 wt% to about 70 wt%, about 1 wt% to about 60 wt%, about 1 wt% to about 50 wt%, about 1 wt% to about 40 wt%, about 1 wt% to about 30 wt%, about 5 wt% to about 95 wt%, about 5 wt% to about 90 wt%, about 5 wt% to about 80 wt%, about 5 wt% to about 70 wt%, about 5 wt% to about 60 wt%, about 5 wt% to about 50 wt%, about 5 wt% to about 40 wt%, about 5 wt% to about 30 wt%, about It may have a value within the range of 10 wt% to about 95 wt%, about 10 wt% to about 90 wt%, about 10 wt% to about 80 wt%, about 10 wt% to about 70 wt%, about 10 wt% to about 60 wt%, about 10 wt% to about 50 wt%, about 10 wt% to about 40 wt%, about 10 wt% to about 30 wt%, about 10 wt% to about 25 wt%, etc.In some embodiments, the amount of hard carbon in the composite material may be about 1 wt%, about 5 wt%, about 10 wt%, about 20 wt%, about 30 wt%, about 40 wt%, about 50 wt%, or more than about 50 wt%. In certain embodiments, the hard carbon phase is substantially amorphous. In other embodiments, the hard carbon phase is substantially crystalline. In further embodiments, the hard carbon phase comprises amorphous and crystalline carbon. The hard carbon phase may be the matrix phase of the composite material. The hard carbon may also be embedded in the pores of silicon-containing additives. The hard carbon may react with some additives to form some material at the interface. For example, there may be a silicon carbide layer between the silicon particles and the hard carbon.
[0039] In certain embodiments, heating the mixture to a desired pyrolysis temperature can further modify the surface of the silicon particles present in the mixture. In some embodiments, pyrolyzing the mixture can form a surface coating on at least 50% of the silicon particles present in the mixture. In some embodiments, pyrolyzing the mixture can form a surface coating on at least 60%, 70%, 80%, 90%, or 99% of the silicon particles present in the mixture. In some embodiments, the surface coating forms a substantially continuous layer on the silicon particles.
[0040] In some embodiments, a carbonization precursor or resin may come into contact with the surface of silicon particles. In certain embodiments, the carbonization precursor coming into contact with the surface of the silicon particles may be one or more types of carbon phases resulting from the thermal decomposition of the precursor. One or more types of carbon phases of the carbonization precursor coming into contact with the surface of the silicon particles may react with the silicon particles during thermal decomposition to form silicon carbide on the surface of the silicon particles. Accordingly, in some embodiments, the surface coating may comprise carbon, silicon carbide, and / or a mixture of carbon and silicon carbide.
[0041] In some embodiments, as further described below, the silicon particles present in the mixture are natural silicon oxide (SiO, SiO2, SiO2). x ) may include a surface layer. In certain embodiments, a carbide precursor in contact with the surface of the silicon particle may react with a naturally occurring natural silicon oxide surface layer to form silicon carbide. In some embodiments, the carbide precursor in contact with the surface of the silicon particle may react with substantially all of the natural silicon oxide layer to form silicon carbide. Thus, the surface coating of the silicon particle may include carbon and silicon carbide in some embodiments, wherein the surface coating is substantially free of silicon oxide. In some embodiments, a first portion of the surface coating may include silicon carbide, while a second portion may include a mixture of silicon carbide and carbon. In some other embodiments, the carbide precursor in contact with the surface of the silicon particle may not completely convert the natural silicon oxide layer into silicon carbide, and the resulting surface coating or coatings may include carbon, silicon carbide, and SiO, SiO2, and SiO2. x It may include one or more silicon oxides such as. In some embodiments, the carbide precursor in contact with the silicon particle surface may react completely to produce a surface coating containing silicon carbide. In some embodiments, substantially all of the surface coating may contain silicon carbide. In some embodiments, such surface coatings may be substantially free of silicon oxide and / or carbon.
[0042] In certain embodiments, the pyrolyzed mixture may produce a silicon-carbon-silicon carbide (e.g., at least one first phase comprising silicon, at least one second phase comprising carbon, and at least one third phase comprising silicon carbide) or silicon-carbon-carbon-silicon carbide (e.g., at least one first phase comprising silicon, at least one second phase comprising carbon, at least one third phase comprising carbon, and at least one fourth phase comprising silicon carbide) composite material comprising silicon particles having a carbon and / or silicon carbide surface coating.
[0043] Additionally, the surface coating of the silicon particles described herein can help limit the external expansion of the silicon particles during lithiation. By limiting external particle expansion during lithiation, the surface coating can help prevent mechanical failure of the silicon particles and ensure excellent electrical contact. The surface coating can further enhance electron charge transfer within the electrode. Controlled and optimized surface modification of the silicon particles at the anode can also significantly improve capacity retention during the cycling of the relevant battery cell.
[0044] Furthermore, surface coatings substantially influence the reactions occurring between the anode material and the electrolyte within the battery. Surface coatings can help reduce unwanted reactions. By forming a surface coating during high-temperature pyrolysis and removing unwanted native oxide (SiO2) through conversion into more stable and non-reactive SiC, higher reversible capacity can be provided while minimizing irreversible capacity loss. Irreversible capacity loss can occur due to the formation and accumulation of a solid electrolyte interface (SEI) layer that consumes lithium. This becomes a more pronounced problem for silicon particles because nano- and micro-scale silicon particles have large surface areas, while larger silicon particles tend to be crushed during lithiation and delithiation, which can introduce additional particle surface area. Additionally, irreversible capacity loss can occur due to the undesirable reaction between native silicon oxide and lithium (Equation 1), which is unavoidable during the processing and storage of silicon anode materials.
[0045] SiO x + yLi + ye → Si + Li y O x (Equation 1)
[0046] Therefore, surface modification of silicon particles by carbon and / or silicon carbide can help form a relatively stable solid electrolyte interface layer and can reduce or eliminate the undesirable reaction between the natural silicon oxide on the surface of the Si particles and lithium (Equation 1).
[0047] FIG. 1b is a schematic diagram of forming silicon carbide on silicon particles as described above. Initially, silicon particles comprising a natural silicon oxide surface layer are provided to a mixture comprising the aforementioned precursor. In some embodiments, the mixture is pyrolyzed in a reducing atmosphere. For example, a reducing atmosphere comprising H2, CO, or hydrocarbon gas, a vacuum, and / or a flowing gas may be used. In some embodiments, the mixture is heated to about 500°C to about 1350°C. In some embodiments, the mixture is heated to about 800°C to about 1200°C. In some embodiments, the mixture is heated to about 1175°C.
[0048] A pyrolyzed precursor in contact with the surface of a silicon particle reacts with the natural silicon oxide layer of the silicon particle to form silicon carbide. The carbide precursor in contact with the surface of the silicon particle is depicted herein as continuous and conformal, but in some other embodiments, it may not be continuous or conformal. Additionally, in some embodiments, the silicon carbide layer formed from the reaction between the carbide precursor in contact with the surface of the silicon particle and the natural silicon oxide layer may take the form of a dispersion or coating within a composite anode film. As shown in FIG. 1b, in some embodiments, the silicon carbide may not be continuous or conformal on the silicon particle, but in some other embodiments, the silicon carbide may be a continuous and / or conformal coating.
[0049] In certain embodiments, graphite particles are added to the mixture. Advantageously, graphite may be an elastically deformable material capable of responding to volume changes of silicon particles as well as being electrochemically active in the battery. Because of its low irreversible capacity, graphite is a preferred active anode material for certain classes of lithium-ion batteries currently on the market. Additionally, graphite is softer than hard carbon and can better absorb volume expansion of silicon additives. In certain embodiments, the particle size (e.g., diameter or maximum dimension) of the graphite particles may be about 0.5 microns to about 20 microns. All, substantially all, or at least some of the graphite particles may have the particle size (e.g., diameter or maximum dimension) described herein. In some embodiments, the average or median particle size (e.g., diameter or maximum dimension) of the graphite particles may be about 0.5 microns to about 20 microns. In some embodiments, the graphite particles may have a particle size distribution. For example, at least about 95%, at least about 90%, at least about 85%, at least about 80%, at least about 70%, or at least about 60% of the particles may have the particle size described herein. In certain embodiments, the composite material may contain graphite particles in an amount greater than 0 wt% and less than about 80 wt%, and may contain graphite particles in an amount including about 40 wt% to about 75 wt%, about 5 wt% to about 30 wt%, about 5 wt% to about 25 wt%, about 5 wt% to about 20 wt%, about 5 wt% to about 15 wt%, etc.
[0050] In certain embodiments, conductive particles that may be electrochemically active are added to the mixture. These particles may enable more electronically conductive composites as well as more mechanically deformable composites capable of absorbing large volume changes occurring during lithiation and delithiation. In certain embodiments, the particle size (e.g., diameter or maximum dimension) of the conductive particles may be from about 10 nanometers to about 7 micrometers. All, substantially all, or at least some of the conductive particles may have the particle size (e.g., diameter or maximum dimension) described herein. In some embodiments, the average or median particle size (e.g., diameter or maximum dimension) of the conductive particles may be from about 10 nm to about 7 micrometers. In some embodiments, the conductive particles may have a distribution of particle sizes. For example, at least about 95%, at least about 90%, at least about 85%, at least about 80%, at least about 70%, or at least about 60% of the particles may have the particle size described herein.
[0051] In certain embodiments, the mixture may contain conductive particles in an amount greater than 0 weight% and less than or equal to about 80 weight%. In further embodiments, the composite material may contain about 45 weight% and less than or equal to about 80 weight%. The conductive particles may be conductive carbons, including carbon black, carbon fibers, carbon nanofibers, carbon nanotubes, etc. Many carbons considered as conductive additives that are not electrochemically active become active when thermally decomposed in the polymer matrix. Alternatively, the conductive particles may be metals or alloys, including copper, nickel, or stainless steel.
[0052] In certain embodiments, the electrode may comprise the composite material described herein. For example, the composite material may form a self-supporting monolithic electrode. The pyrolyzed carbon phase of the composite material (e.g., hard carbon phase) may be held together and may structurally support particles added to the mixture. In certain embodiments, the self-supporting monolithic electrode does not comprise a separate current collector layer and / or other supporting structure. In some embodiments, the composite material and / or electrode does not comprise a polymer exceeding a trace amount remaining after the pyrolysis of the precursor. In further embodiments, the composite material and / or electrode does not comprise a non-electrically conductive binder. The composite material may also comprise porosity, for example, about 1% to about 70% or about 5% to about 50% by volume. For example, the porosity may be about 5% to about 40% by volume.
[0053] In some embodiments, the composite material may be attached to a current collector. In some embodiments, the composite material may also be formed into a powder. For example, the composite material may be ground into a powder. The composite material powder may be used as an active material for the electrode. For example, the composite material powder may be deposited on the current collector in a manner similar to how conventional electrode structures known in the industry are formed.
[0054] In certain embodiments, the electrodes of the battery or electrochemical cell may comprise a composite material comprising a composite material having silicon particles as described herein. For example, the composite material may be used for the anode and / or cathode. In certain embodiments, the battery is a lithium-ion battery. In additional embodiments, the battery is a secondary battery, or in other embodiments, the battery is a primary battery.
[0055] Additionally, to improve battery life, the full capacity of the composite material (e.g., the number of charge and discharge cycles before the battery fails or its performance drops below a usage level) may not be utilized during battery use. For example, a composite material having about 70 wt% silicon particles, about 20 wt% carbon from a precursor, and about 10 wt% graphite may have a maximum weight capacity of about 3000 mAh / g, whereas the composite material may be used only up to a weight capacity of about 550 mAh / g to about 1500 mAh / g. Although the maximum weight capacity of the composite material may not be utilized, using the composite material at a lower capacity may still achieve a higher capacity than that of a specific lithium-ion battery. In certain embodiments, the composite material is used at a weight capacity of less than about 70% of the composite material's maximum weight capacity, or is used only at this weight capacity. For example, the composite material is not used at a weight capacity exceeding about 70% of the composite material's maximum weight capacity. In additional embodiments, the composite material is used at a weight capacity of less than about 50% of the maximum weight capacity of the composite material or less than about 30% of the maximum weight capacity of the composite material, or is used only at this weight capacity.
[0056] silicon particles
[0057] Silicon particles for use in battery electrodes (e.g., anodes and cathodes) are described herein. Anode electrodes currently used in rechargeable lithium-ion cells generally have a specific capacity of about 200 milliampere-hours per gram (including metal foil current collectors, conductive additives, and binder materials). Graphite, the active material used in most lithium-ion battery anodes, has a theoretical energy density of 372 milliampere-hours / gram (mAh / g). In comparison, silicon has a higher theoretical capacity of 4200 mAh / g. However, silicon expands by more than 300% upon lithium insertion. Due to this expansion, silicon-containing anodes must be able to expand while allowing the silicon to maintain electrical contact with the silicon.
[0058] Some embodiments provide silicon particles that can be used as an electrochemically active material in an electrode. In addition to the silicon particles, the electrode may include a binder and / or other electrochemical active materials. For example, the silicon particles described herein may be used as silicon particles in the composite material described herein. In another example, the electrode may have a layer of electrochemical active material on a current collector, and the electrochemical active material layer comprises silicon particles. The electrochemical active material may also include one or more types of carbon.
[0059] Advantageously, the silicon particles described herein can improve the performance of an electrochemical active material, such as improving capacity and / or cycling performance. Additionally, an electrochemical active material containing such silicon particles may not be significantly degraded due to the lithiation of the silicon particles.
[0060] In certain embodiments, silicon particles may have an average particle size of about 10 nm to about 40 µm, e.g., an average diameter or average maximum dimension, as described herein. Further embodiments may include average particle sizes of about 1 µm to about 15 µm, about 10 nm to about 1 µm, and about 100 nm to about 10 µm. Silicon particles of various sizes may be separated by various methods, such as air separation, sieving, or other screening methods. For example, a mesh size of 325 may be used to separate particles having a particle size smaller than about 44 µm from particles having a particle size larger than about 44 µm.
[0061] Additionally, silicon particles may have a distribution of particle sizes. For example, at least about 90% of the particles may have particle sizes of, for example, about 10 nm to about 40 µm, about 1 µm to about 15 µm, about 10 nm to about 1 µm, and / or a diameter or maximum dimension greater than about 200 nm.
[0062] In some embodiments, the silicon particles may have an average surface area per unit mass of about 1 m² / g to about 100 m² / g, about 1 m² / g to about 80 m² / g, about 1 m² / g to about 60 m² / g, about 1 m² / g to about 50 m² / g, about 1 m² / g to about 30 m² / g, about 1 m² / g to about 10 m² / g, about 1 m² / g to about 5 m² / g, about 2 m² / g to about 4 m² / g, or less than about 5 m² / g.
[0063] In certain embodiments, the silicon particles are at least partially crystalline, substantially crystalline, and / or completely crystalline. Additionally, the silicon particles may be substantially pure silicon.
[0064] Compared to silicon particles used in conventional electrodes, the silicon particles described herein in some embodiments may generally have a larger average particle size. In some embodiments, the average surface area of the silicon particles described herein may generally be smaller. Without being bound by any specific theory, the lower surface area of the silicon particles described herein may contribute to the improved performance of electrochemical cells. A typical lithium-ion type rechargeable battery anode contains nano-sized silicon particles. As part of efforts to further increase the capacity of the cell, smaller silicon particles (e.g., silicon particles in the nano-size range) are used to make the electrode active material. In some cases, silicon particles are milled to reduce particle size. Sometimes, milling can cause the particle surface to become rough or scratched, which also increases the surface area. However, the increased surface area of the silicon particles can actually contribute to increased irreversible capacity loss by increasing the degradation of the electrolyte. Figures 2a and 2b are SEM micrographs of exemplary embodiments of silicon particles milled from larger silicon particles. As illustrated in the drawing, certain embodiments may have a roughened surface.
[0065] As described in this specification, certain embodiments include silicon particles having surface roughness in the nanometer size range, for example, micron-sized silicon particles having nanometer-sized features on their surface. FIGS. 2c and 2d are SEM micrographs of exemplary embodiments of such silicon particles. Various of these silicon particles may have a surface comprising an average particle size (e.g., average diameter or average maximum dimension) in the micron range (e.g., as described herein, about 0.1 µm to about 30 µm) and nanometer-sized features (e.g., as described herein, about 1 nm to about 1 µm, about 1 nm to about 750 nm, about 1 nm to about 500 nm, about 1 nm to about 250 nm, about 1 nm to about 100 nm, about 10 nm to about 500 nm, about 10 nm to about 250 nm, about 10 nm to about 100 nm, about 10 nm to about 75 nm, or about 10 nm to about 50 nm). The features may comprise silicon.
[0066] Compared to the exemplary embodiments shown in FIGS. 2a and 2b, silicon particles having a combined micron / nanometer-sized geometry (e.g., FIGS. 2c and 2d) may have a larger surface area than milled particles. Thus, the silicon particles used can be determined according to the desired application and specifications.
[0067] Even if a specific embodiment of the silicon particle has nanometer-sized features on its surface, the total surface area of the particle may be more similar to that of a micron-sized particle than to that of a nanometer-sized particle. For example, micron-sized silicon particles (e.g., silicon milled from large particles) generally have an average surface area per unit mass greater than about 0.5 m² / g and less than about 2 m² / g (e.g., using the Brunauer Emmet Teller (BET) particle surface area measurement method), whereas nanometer-sized silicon particles generally have an average surface area per unit mass greater than about 100 m² / g and less than about 500 m² / g. In the specific embodiments described herein, the average surface area per unit mass is about 1 m² / g to about 30 m² / g, about 1 m² / g to about 25 m² / g, about 1 m² / g to about 20 m² / g, about 1 m² / g to about 10 m² / g, about 2 m² / g to about 30 m² / g, about 2 m² / g to about 25 m² / g, about 2 m² / g to about 20 m² / g, about 2 m² / g to about 10 m² / g, about 3 m² / g to about 30 m² / g, about 3 m² / g to about 25 m² / g, about 3 m² / g to about 20 m² / g, about 3 m² / g to about 10 m² / g (e.g., about 3 m² / g to about 6 m² / g), about 5 m² / g to about 30 m² / g, about 5 m² / g to about 25 m² / g, about 5 m² / g It may be up to about 20 m² / g, about 5 m² / g to about 15 m² / g, or about 5 m² / g to about 10 m² / g.
[0068] Various examples of micron-sized silicon particles having nanometer-sized features can be used to form specific embodiments of the composite material described herein. For example, FIG. 2e illustrates an exemplary method (200) for forming a specific embodiment of the composite material. The method (200) includes the step (block (210)) of providing a plurality of silicon particles (e.g., silicon particles having a surface having an average particle size of about 0.1 μm to about 30 μm and nanometer-sized features). The method (200) further includes the step (block (220)) of forming a mixture comprising a precursor and a plurality of silicon particles. The method (200) further includes the step of pyrolyzing the precursor (block (230)) to convert the precursor into one or more types of carbon phases to form the composite material.
[0069] In relation to block (210) of the method (200), silicon having the characteristics described herein may be synthesized as a product or byproduct of a Fluidized Bed Reactor (FBR) process. For example, a useful material in the FBR process may be grown on a seed silicon material. Generally, particles may be removed from the reactor by gravity. Some fine particulate silicon materials may exit the reactor from the top of the reactor or be deposited on the reactor walls. The material exiting the top of the reactor or being deposited on the reactor walls (e.g., byproduct material) may have nanoscale features on microscale particles. In some of these processes, a gas (e.g., a nitrogen carrier gas) may pass through the silicon material. For example, the silicon material may be a plurality of granular silicon. The gas may pass through the silicon material at a speed high enough to suspend the solid silicon material and cause it to behave like a fluid. The process may be carried out under an inert atmosphere, for example, nitrogen or argon. In some embodiments, silane gas may also be used to grow metallic silicon, for example, on the surface of silicon particles. The gaseous growth process can impart unique surface properties to the silicon particles, such as nanometer-sized features. Since silicon is generally split into smooth shapes like glass, certain embodiments of silicon particles formed using the FBR process can advantageously obtain small features, for example, in the nanometer-sized range, which are not easily achieved in some embodiments of silicon particles formed by milling from larger silicon particles.
[0070] In addition, since the FBR process can be performed in an inert atmosphere, particles of very high purity (e.g., purity exceeding 99.9999%) can be achieved. In some embodiments, purity of about 99.9999% to about 99.999999% can be achieved. In some embodiments, the FBR process may be similar to the process used to produce solar-grade polysilicon using 85% less energy than the traditional Siemens method, in which trichlorosilane decomposes at 1150°C to form polysilicon by depositing additional silicon material onto high-purity silicon rods. Since nanometer-sized silicon particles have been shown to increase cycle life performance in electrochemical cells, micron-sized silicon particles have not been considered for use as electrochemical active materials in electrochemical cells.
[0071] With respect to blocks (220 and 230) of the method (200), the step of forming a mixture comprising a precursor and a plurality of silicon particles (block (220)), and the step of pyrolyzing the precursor (block (230)) to convert the precursor into one or more types of carbon phases to form a composite material may each be similar to blocks (101 and 105) of the method (100) described herein. In some embodiments, pyrolysis (e.g., from about 900°C to about 1350°C) occurs at a temperature below the melting point of silicon (e.g., about 1414°C) without affecting the nanometer-sized features of the silicon particles.
[0072] According to specific embodiments described in this specification, specific micron-sized silicon particles having nanometer surface features can achieve high energy density and can be used in electrodes and / or composite materials for use in electrochemical cells to improve performance during cell cycling.
[0073] Surface modification of silicon particles
[0074] As described herein, silicon particles can be used as electrochemical active materials in electrodes. In some embodiments, silicon particles can be used in silicon-carbon composite electrodes. The electrode can be formed by pyrolyzing a mixture comprising a carbon precursor and silicon particles to convert the carbon precursor into one or more carbon phases, thereby forming a composite film having silicon particles distributed across the composite film. Without being bound by theory, the surface of the silicon particles can be modified to improve wettability with the carbon precursor, thereby improving adhesion with the carbon precursor and reducing the amount of porosity at the silicon-carbon interface. Consequently, the silicon-carbon composite electrode can have greater physical strength, greater conductivity, and better cycling performance in the battery.
[0075] FIG. 3a schematically illustrates exemplary surface-modified silicon particles (300) that can be used as an active material in a silicon composite electrode, for example, in a lithium-ion battery. The exemplary silicon particles (300) comprise a bulk material (301) and a surface (302). The surface (302) may be modified by a silane treatment, which is represented by Si-O-Si bonds on the surface (302) and further described. For simplification, the bonds are represented as Si-O-Si-R, but may include other bonds, elements, and / or functional groups.
[0076] For simplification, the silicon particles (300) of FIG. 3a are depicted as having a circular cross-sectional shape, such as spherical or cylindrical particles. However, it is understood that the "silicon particles" (300) described herein may have any regular or irregular cross-sectional shape and are not limited to spherical or cylindrical particles. The silicon particles (300) may have any size as described herein, for example, a maximum diameter or dimension of about 10 nm to about 50 µm, a maximum diameter or dimension of about 1 µm to about 50 µm, etc.
[0077] Referring further to FIG. 3a, the bulk material (301) may have any of the properties of any silicon particles described herein. For example, the bulk material (301) may or may not be pure silicon. For example, the bulk material (301) may be substantially silicon or a silicon alloy (e.g., silicon as a major component together with one or more other elements). In some embodiments, the bulk material (301) may be about 90% pure silicon to about 99.9999% pure silicon. In some cases, the bulk material (301) may be substantially pure silicon. In some embodiments, the bulk material (301) may be at least partially crystalline, substantially crystalline, and / or completely crystalline. In some cases, the surface (302) may include a natural and / or artificially generated oxide layer (e.g., SiO, SiO2, SiOx, SiOH). Surface oxidation can be performed in the presence or absence of water, for example at about 100°C to about 1200°C.
[0078] In various embodiments, the surface (302) may be modified using one or more silicon-containing organic compounds, e.g., organosilanes. In some cases, the organosilane may react with natural and / or artificially generated oxides of silicon. For example, one or more organosilanes may react with the silanol groups of the silicon surface (302) to form a bond (e.g., Si-O-Si) between the silanol groups and the organosilane. The organosilane may include various functional groups, including but not limited to silanol (R-Si-OH), silyl ether (R-Si-OR'), silyl chloride (R-Si-Cl), dialkylaminosilane (R-Si-NR2), silyl hydride (R-SiH3), and / or cyclic azasilane.
[0079] The "R" region of an organosilane may have one or more functional groups tailored to specific components used in manufacturing silicon composite electrodes. For example, to improve bonding and wetting with polyimide materials, aminoalkyl functional groups such as those present in 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane (AEAPTMS), or 2,2-dimethoxy-1,6-diaza-2-silacyclooctane may be used. The molecular structure of 3-aminopropyltriethoxysilane, a silyl ether with an amine functional group, is as follows:
[0080]
[0081] The molecular structure of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, a silyl ether having a diamine functional group, is as follows:
[0082]
[0083] The molecular structure of the cyclic azasilane 2,2-dimethoxy-1,6-diaza-2-silacyclooctane is as follows:
[0084]
[0085] Epoxide linkers can be used to improve bonding and wetting with phenolic resins. The molecular structure of 5,6-epoxyhexyltriethoxysilane, an exemplary epoxide linker that is a silyl ether having an epoxide functional group, is as follows:
[0086]
[0087] For materials containing polycyclic aromatic hydrocarbons (e.g., pitch or tar, etc.), organosilanes having aromatic functional groups may be used. An example of such an organosilane is benzyltriethoxysilane, a silyl ether having aromatic functional groups. Its molecular structure is as follows:
[0088]
[0089] In some embodiments, the organosilane may include a silyl hydride (R-SiH3). For example, the molecular structure of dodecylsilane is as follows:
[0090]
[0091] In some embodiments, the organosilane may include dialkylaminosilane (R-Si-NR2). For example, the molecular structure of (N,N-dimethylamino)trimethylsilane is as follows:
[0092]
[0093] In various embodiments, the silane-treated silicon particles (300) may comprise a silicon oxide surface that reacts with one or more organosilanes. For example, the surface (302) of the silicon particles (300) may comprise a bond between a surface silanol group and an organosilane. Different reaction mechanisms may exist for each class of organosilanes. Without being bound by theory, the general principle is that the silanol group on the silicon particle surface (302) participates in a nucleophilic substitution reaction with the organosilane. In the case of silyl chlorides, the reaction may occur through the substitution of chloride groups to form a new Si-O-Si bond between the silicon particles and the organosilane, thereby producing HCl as a byproduct. In the case of silyl ethers, the reaction mechanism may involve a similar direct substitution reaction to produce an alcohol. Alternatively or additionally, the reaction mechanism may include a two-step mechanism comprising 1) hydrolyzing the silyl ether to produce an alcohol and a silanol, and 2) forming a new Si-O-Si bond and water as a byproduct through a condensation reaction between the organosilanol and the particle surface silanol. A similar nucleophilic substitution reaction mechanism may be applied to dialkylaminosilanes (e.g., Si-O-Si and secondary amine formation), silyl hydrides (e.g., hydrogen formation), or cyclic azasilanes (e.g., rearrangement to form linear organosilanes). Polyfunctional silyl ethers (e.g., AEAPTMS) or silans may participate in a specific amount of polymerization on the silicon surface because each silanol (or hydrolyzed silyl ether) can condense with other silans to form Si-O-Si.
[0094] Surface modification can be performed using various approaches. In some examples, silicon may be suspended in a heated liquid containing a specific concentration of organosilane. In some cases, the liquid may be heated to a temperature in the range of about 50°C to about 200°C or any range within this range (e.g., about 50°C to about 100°C, about 50°C to about 150°C, about 50°C to about 175°C, about 75°C to about 200°C, about 100°C to about 200°C, about 150°C to about 200°C, etc.). This method can be used for silyl ethers and silyl chlorides. The liquid may be water, an organic solvent, or a mixture of water and an organic solvent. In some cases, water may be used for silyl ethers. In some cases, little or no water may be used for silyl chlorides. As another example, silicon can be modified by exposure to organosilane vapor, for example, while diffusing into a thin layer in a tray or while stirring in a reactor vessel. Other examples are also possible.
[0095] The amount of organosilane may be related to the specific surface area of the silicon and / or the non-wetting surface of the organosilane. For example, a silicon material with a specific surface area of 0.6 m² / g and an organosilane with a non-wetting surface of 358 m² / g may use a ratio of about 1.68 g of organosilane per kilogram of silicon in some cases.
[0096] As described herein, specific embodiments of composite materials as described herein can be formed using various examples of silane-treated silicon particles. For example, the composite material may be used as an electrode for use in an electrochemical cell.
[0097] Certain embodiments may include a composite membrane. The composite membrane may include any of the embodiments of the composite membrane described herein. For example, the composite membrane may have silicon particles of greater than 0 wt% to about 99 wt% (e.g., about 50 wt% to about 99 wt%, about 60 wt% to about 99 wt%, about 70 wt% to about 99 wt%, about 75 wt% to about 99 wt%, about 80 wt% to about 99 wt%, etc.), or silicon particles of greater than 0 wt% to about 95 wt% (e.g., about 50 wt% to about 95 wt%, about 60 wt% to about 95 wt%, about 70 wt% to about 95 wt%, about 75 wt% to about 95 wt%, about 80 wt% to about 95 wt%, etc.). Silicon particles may include surface-treated silicon particles and / or a combination of surface-treated silicon particles and untreated silicon particles. The treated or untreated silicon particles may include any of the silicon particles described herein (e.g., silicon particles with an average particle size of about 0.1 μm to about 40 μm, silicon particles with an average particle size of about 1 μm to about 20 μm, micron-sized silicon particles having nanometer-sized features, etc.).
[0098] The organic portion of an organosilane can interact with a carbon precursor through various mechanisms, for example, depending on which organosilane and which precursor are used. For example, an organosilane having a primary amine group (e.g., AEAPTMS) can react with a precursor containing a carboxylic acid group (e.g., polyamic acid) to form an amide bond. Other interactions are also possible. Using the same example of AEAPTMS and polyamic acid (or polyimide), the primary amine group of the organosilane can participate in hydrogen bonding with the carbonyl group of the polyamic acid (or polyimide).
[0099] Without being bound by theory, Si-O-Si bonds are relatively thermally stable, so, for example, at least a Si-O-Si monolayer may remain on the surface of silicon particles after pyrolysis at about 900°C to about 1350°C. In the case of polyfunctional silyl ethers, the thickness of the Si-O-Si domains may be several layers depending on the reaction conditions. The organic portion of the organosilane may pyrolyze according to a mechanism similar to that of carbon precursors to form hydrogen gas, water, carbon monoxide, carbon dioxide, cyanide, and / or carbon depending on the composition and conditions.
[0100] The composite membrane may also have one or more types of carbon phases in an amount greater than 0 weight% to about 90 weight%. One or more types of carbon phases may be substantially continuous phases. In some cases, the continuous phase may hold the composite membrane together. In some embodiments, one or more types of carbon phases may be electrochemically active and / or electrically conductive. In some embodiments, silicon particles may be distributed across the composite membrane.
[0101] As described herein, silicon particles may have a surface coating. In some embodiments, the surface coating may cover at least about 50%, 60%, 70%, 80%, 90%, or 99% of the silicon particles. In some embodiments, the surface coating may be a substantially continuous layer. In some embodiments, the surface coating is silicon monoxide (SiO), silicon dioxide (SiO2), and / or silicon oxide (SiO2). x It may include ). During pyrolysis, some, substantially all or all of the silicon oxide on the surface of the silicon particles may be converted into silicon carbide.
[0102] In various embodiments, the composite film may comprise an interfacial region between silicon particles and one or more types of carbon phases. The interfacial region may comprise silicon, carbon, silicon oxide, silicon carbide, silicon oxycarbide, or a mixture of these materials with or without a dopant. The modified surface of the silicon particles may improve wettability with the carbon precursor, thereby improving adhesion with the carbon precursor and reducing porosity at the silicon-carbon interface. In some embodiments, the interfacial region may have porosity of about 30% or less, 25%, 20%, 15%, 10%, or 5%. Advantageously, having less porosity may increase the strength and conductivity of the composite material. In various embodiments, the composite film may be self-supporting. In some embodiments, the composite film may be attached to a current collector. The composite film may be used as an electrode (e.g., an anode or a cathode).
[0103] FIG. 3b illustrates an exemplary method (400) for forming a specific embodiment of a composite material. The method (400) may include the step (block (410)) of providing a mixture comprising a carbon precursor and silane-treated silicon particles. The method (400) may also include the step (420) of converting the precursor into one or more types of carbon phases, for example, by pyrolyzing the precursor.
[0104] In relation to block (410) of the method (400), silane-treated silicon particles may be added to a mixture containing a carbon precursor. The silicon particles may be silane-treated using any embodiment described herein. In some of these embodiments, as described herein, the carbon precursor may include a polymer and a solvent. The polymer and solvent may include any polymer and solvent described herein.
[0105] As described herein, the method (400) may also include various steps such as casting a mixture onto a substrate, drying the mixture to form a film, removing the film from the substrate, and placing the film in a high-temperature press. In relation to block (420) of the method (400), the carbon precursor may be pyrolyzed as described herein to convert the precursor into one or more types of carbon phases. Silicon particles may be distributed across the composite film.
[0106] As described herein, silane-surface-treated silicon particles may have better wettability with polymer binder solutions and a greater ability to adhere to polymer materials. Advantageously, the adhesion can withstand thermal decomposition. In silicon-carbon composites, this can translate, for example in lithium-ion batteries, into less porosity, greater physical strength, and / or better cycling performance. Without being bound by theory, an increased SiO2 region from a polyfunctional silyl ether can create an increased SiC region that can provide additional structural integrity to various embodiments of the silicon composite. In many cases, adding an interfacial layer between silicon and carbon does not increase electrical resistance or impair electrochemical performance. Additionally, the Si-O of the silane can be reduced to form SiC, which can help reduce Li loss to the SEI layer according to Equation 1.
[0107] Examples
[0108] The following exemplary process for manufacturing an anode generally involves mixing the components together, casting these components onto a removable substrate, drying and curing them, removing the substrate, and then pyrolyzing the resulting sample. Typically, N-methyl-2-pyrrolidone (NMP) is used as a solvent to modify the viscosity of the mixture, and a doctor blade method is used to make it castable.
[0109] Example 1
[0110] In Example 1, a polyimide liquid precursor (PI 2611 from HD Microsystems), graphite particles (SLP30 from Timcal), conductive carbon particles (Super P from Timcal), and silicon particles (Alfa Aesar) were mixed together for 5 minutes using a Spex 8000D machine in a weight ratio of 200:55:5:20. The mixture was then cast onto aluminum foil and dried in a 90°C oven to remove the solvent (e.g., NMP). A curing step was then performed in a high-temperature press at 200°C under negligible pressure for at least 12 hours. The aluminum foil backing was then removed by etching in a 12.5% HCl solution. The remaining film was rinsed with deionized water, dried, and then pyrolyzed at 1175°C under an argon flow for about 1 hour. This process produced a composition of 15.8% PI 2611-derived carbon, 57.9% graphite particles, 5.3% Super P-derived carbon, and 21.1% silicon by weight.
[0111] Then, the generated electrode was tested in a pouch cell configuration against a lithium NMC oxide cathode. A typical cycling graph is shown in Fig. 4.
[0112] Example 2
[0113] In Example 2, silicon particles (EVNANO Advanced Chemical Materials Co. Ltd.) were initially mixed with NMP in a 1:9 weight ratio using a Turbula mixer for 1 hour. Then, a polyimide liquid precursor (PI 2611 from HD Microsystems), graphite particles (SLP30 from Timcal), and carbon nanofibers (CNF from Pyrograf) were added to the Si:NMP mixture in a weight ratio of 200:55:5:200 and vortexed for about 2 minutes. The mixture was then cast onto an aluminum foil covered with a 21 µm thick copper mesh. The sample was then dried in a 90°C oven to remove the solvent, such as NMP. A curing step was then performed in a high-temperature press at 200°C under negligible pressure for at least 12 hours. The aluminum foil backing was then removed by etching in a 12.5% HCl solution. Then, the remaining membrane was rinsed with deionized water and dried, and then pyrolyzed at 1000°C for about 1 hour under argon. This process produced a composition of 15.8% PI 2611-derived carbon, 57.9% graphite particles, 5.3% CNF, and 21.1% silicon by weight.
[0114] Then, the generated electrode was tested in a pouch cell configuration against a lithium NMC oxide cathode. A typical cycling graph is shown in Fig. 5.
[0115] Example 3
[0116] In Example 3, a polyimide liquid precursor (PI 2611 from HD Microsystems) and 325 mesh silicon particles (Alfa Aesar) were mixed together in a weight ratio of 40:1 for 1 hour using a Turbula mixer. The mixture was then cast onto aluminum foil and dried in a 90°C oven to remove the solvent (e.g., NMP). A curing step was then performed in a high-temperature press at 200°C under negligible pressure for at least 12 hours. The aluminum foil backing was then removed by etching in a 12.5% HCl solution. The remaining film was rinsed with deionized water, dried, and then pyrolyzed at 1175°C under an argon flow for about 1 hour. This process produced a composition of 75% carbon derived from PI 2611 and 25% silicon by weight.
[0117] Then, the generated electrode was tested in a pouch cell configuration against a lithium NMC oxide cathode. A typical cycling graph is shown in Fig. 6.
[0118] Example 4
[0119] In Example 4, silicon microparticles (Alfa Aesar), polyimide liquid precursor (HD Microsystems PI 2611), graphite particles (Timcal SLP30), milled carbon fibers (Fibre Glast Developments), carbon nanofibers (Pyrograf CNF), carbon nanotubes (CNANO Technology Limited), conductive carbon particles (Timcal Super P), and conductive graphite particles (Timcal KS6) were mixed using a vortexer for 5 minutes in a weight ratio of 20:200:30:8:4:2:1:15. The mixture was then cast onto an aluminum foil. The sample was then dried in a 90°C oven to remove a solvent such as NMP. A curing step was then performed in a high-temperature press at 200°C under negligible pressure for at least 12 hours. The aluminum foil backing was then removed by etching in a 12.5% HCl solution. Then, the remaining membrane was rinsed with deionized water and dried, and then pyrolyzed under argon at 1175°C for about 1 hour. This process produced a composition similar to the original mixture but containing a carbon portion derived from PI 2611, which is 7.5% of the original weight of the polyimide precursor.
[0120] Then, the generated electrode was tested in a pouch cell configuration against a lithium NMC oxide cathode. A typical cycling graph is shown in Fig. 7.
[0121] Example 5
[0122] In Example 5, a polyimide liquid precursor (PI 2611 from HD Microsystems) and silicon microparticles (Alfa Aesar) were mixed together in a weight ratio of 4:1 for 1 hour using a Turbula mixer. The mixture was then cast onto an aluminum foil covered with a carbon veil (Fiber Glast Developments Corporation) and dried in a 90°C oven to remove the solvent, e.g., NMP. A curing step was then performed in a high-temperature press at 200°C under negligible pressure for at least 12 hours. The aluminum foil backing was then removed by etching in a 12.5% HCl solution. The remaining film was rinsed with deionized water, dried, and then pyrolyzed at 1175°C under an argon flow for about 1 hour. Since the weight of the veil is negligible, this process produced a composition of approximately 23% PI 2611-derived carbon and 76% silicon by weight.
[0123] The generated electrode was then tested in a pouch cell configuration against a lithium nickel manganese cobalt oxide (NMC) cathode. A typical cycling graph is shown in Fig. 8.
[0124] Example 6
[0125] In Example 6, a polyimide liquid precursor (PI 2611 from HD Microsystems), graphite particles (SLP30 from Timcal), and silicon microparticles (Alfa Aesar) were mixed together in a weight ratio of 200:10:70 using a Spex 8000D machine for 5 minutes. The mixture was then cast onto aluminum foil and dried in a 90°C oven to remove the solvent (e.g., NMP). The dried mixture was cured in a high-temperature press at 200°C under negligible pressure for at least 12 hours. The aluminum foil backing was then removed by etching in a 12.5% HCl solution. The remaining membrane was rinsed with deionized water, dried, and then pyrolyzed at 1175°C under an argon flow for about 1 hour. This process produced a composition of 15.8% PI 2611-derived carbon, 10.5% graphite particles, and 73.7% silicon by weight.
[0126] The generated electrode was then tested in a pouch cell configuration against a lithium NMC oxide cathode. The anode was charged to 600 mAh / g in each cycle, and the discharge capacity was recorded for each cycle. A typical cycling graph is shown in Fig. 9.
[0127] Example 7
[0128] In Example 7, PVDF and silicon particles (EVNANO Advanced Chemical Materials Co.), conductive carbon particles (Super P of Timcal), conductive graphite particles (KS6 of Timcal), graphite particles (SLP30 of Timcal), and NMP were mixed in a weight ratio of 5:20:1:4:70:95. The mixture was then cast onto a copper substrate and placed in a 90°C oven to remove solvents such as NMP. The resulting electrode was then tested in a pouch cell configuration against a lithium NMC oxide cathode. A typical cycling graph is shown in Fig. 10.
[0129] Example 8
[0130] A number of experiments were conducted to find the effect of changing the percentage of polyimide-derived carbon (e.g., 2611c) while maintaining the percentage of silicon microparticles (Alfa Aesar) at 20 wt% and decreasing the percentage of graphite particles (Timcal's SLP30).
[0131] As illustrated in FIGS. 11a and 11b, the results show that a higher amount of graphite and a lower amount of 2611c have advantages in cell performance by increasing the specific capacity while decreasing the irreversible capacity. Since minimizing 2611c has a negative effect on the strength of the generated anode, a value close to 20 wt% may be desirable as a compromise in one embodiment.
[0132] Example 9
[0133] Similar to Example 8, when 2611c is maintained at 20 wt% and the Si percentage is increased at the expense of graphite particles, the first cycle discharge capacity of the resulting electrode increases. FIG. 12 shows that a higher silicon content can produce an anode with better performance.
[0134] Example 10
[0135] When a polyimide sheet with a thickness of 1 mil is pyrolyzed and tested according to the procedure of Example 1, the reversible capacity and irreversible capacity are plotted as a function of the pyrolysis temperature. FIG. 13 indicates that in one embodiment, it is preferable to pyrolyze a polyimide sheet (Upilex of UBE) at about 1175°C.
[0136] Additional example
[0137] Figure 14 is a photograph of a 4.3 cm × 4.3 cm composite anode film without a metal foil support layer. The composite anode film has a thickness of about 30 microns and has a composition of about 15.8% carbon derived from PI 2611 by weight, about 10.5% graphite particles, and about 73.7% silicon.
[0138] Figures 15 to 20 are scanning electron microscope (SEM) images of the composite anode membrane. The composition of the composite anode membrane was approximately 15.8% carbon derived from PI 2611, approximately 10.5% graphite particles, and approximately 73.7% silicon by weight. Figures 15 and 16 show the membrane before cycling (the out-of-focus area is the bottom of the anode, and the in-focus area is the split edge of the composite membrane). Figures 17, 18, and 19 are SEM images of the composite anode membrane after 10 cycles, 10 cycles, and 300 cycles, respectively. The SEM images show that after cycling, there is no significant breakdown of silicon and no excessive layer of solid electrolyte interface / interphase (SEI) built on the top of the anode. Figure 20 is an SEM image of a cross- section of the composite anode membrane.
[0139] The measured characteristics of exemplary silicon particles are described below. These examples are discussed for illustrative purposes only and should not be construed as limiting the scope of the disclosed embodiments.
[0140] Figure 21 is an X-ray powder diffraction (XRD) graph of sample silicon particles. The XRD graph suggests that the sample silicon particles are substantially crystalline or polycrystalline.
[0141] Figures 22 to 25 are scanning electron microscope (SEM) images of sample silicon particles. Although the SEM images appear to show that the silicon particles may have an average particle size larger than the measured average particle size of about 300 nm, it is not bound by theory and is thought that the particles clump together to appear as larger particles.
[0142] Figure 26 is a chemical analysis of the sample silicon particles. The chemical analysis suggests that the silicon particles are substantially pure silicon.
[0143] FIGS. 27a and 27b are histograms of exemplary particle sizes of two micron-sized silicon particles having nanometer-sized features. The particles were prepared by an FBR process. The exemplary silicon particles may have a particle size distribution. For example, at least 90% of the particles may have a particle size, e.g., diameter or maximum dimension of about 5 µm to 20 µm (e.g., about 6 µm to about 19 µm). At least about 50% of the particles may have a particle size of about 1 µm to about 10 µm (e.g., about 2 µm to about 9 µm). Additionally, at least about 10% of the particles may have a particle size of about 0.5 µm to about 2 µm (e.g., about 0.9 µm to about 1.1 µm).
[0144] FIG. 28 is a plot of discharge capacity during cell cycling comparing two types of exemplary silicon particles. The performance of four silicon particle samples (micron-sized particles with nanometer-sized features) manufactured by the FBR process is compared with five silicon particle samples prepared by milling larger silicon particles. Thus, certain embodiments of silicon particles having combined micron / nanometer geometry (e.g., manufactured by the FBR process) may have improved performance compared to various other embodiments of silicon particles (e.g., micron-sized silicon particles manufactured by milling larger particles). The type of silicon particles to be used can be tailored to the intended or desired application and specifications.
[0145] Examples of silane-treated silicon particles
[0146] In one example, 50 g of silicone powder was added to a 1% solution of 3-aminopropyltriethoxysilane in water. The mixture was stirred and reacted at room temperature for 5 minutes. Then, the treated silicone was filtered using filter paper and a Buchner funnel, rinsed with water, and dried under vacuum for 66 hours. The resulting material was mixed into a slurry with polyamic acid resin, graphite, and N-methyl-pyrrolidone (NMP) and coated onto a polyethylene terephthalate (PET) substrate. The resulting "green" silicone composite film was removed from the PET and evaluated, and it was found to have a tensile strength 60% higher than that of a film made in the same way using untreated silicone.
[0147] In another example, silicon was added to a 2% solution of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane in water, refluxed at 100°C for 2 hours, and dried at 200°C for 16 hours. The resulting cake was ground and analyzed by X-ray photoelectron spectroscopy (XPS) to confirm that the surface was modified with organosilane.
[0148] In another example, silicon was placed in a glass container and combined with N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and the ratio of organosilane to silicon was 0.4 wt%. The material was stirred at 90°C under atmospheric pressure for 4 hours. This produced a loosely aggregated powder.
[0149] Figure 29 shows the X-ray photoelectron spectroscopy (XPS) spectral regions of silane-treated and untreated silicon samples. The spectrum for the example treated in water (with or without silane) is labeled "water-treated," and the spectrum for the example placed in a glass container at atmospheric pressure (with or without silane) is labeled "rotovap-processed." The spectra show an increased carbon content for the silane-treated silicon. In Figure 29, the silane-treated silicon subjected to the rotational evaporation process has a higher peak than the silane-treated silicon subjected to the water treatment process. Without being bound by theory, the rotational evaporation process is performed in a sealed container at 90°C so that silane vapor does not escape, thereby increasing the likelihood of reaction with silicon.
[0150] Silane-treated (water-treated and rotary evaporation process-treated) silicon was milled in NMP with a zirconia medium and mixed into a slurry containing NMP, graphite, and polyamic acid resin. The slurry was then coated onto a PET film with a loading of 4.27 mg / cm² (containing 15% solvent content) and densified using a calender. The green film was then removed from the PET, cut into sheets, and vacuum dried using a two-step process (15 hours at 120°C and 5 hours at 220°C). The dried film was heat-treated at 1175°C to convert the polymer matrix into carbon. Separately, a 15 µm thick copper foil was coated with polyamideimide (applied to NMP with a 6 wt% varnish and dried under vacuum at 110°C for 16 hours). A silicon-carbon composite film was laminated onto coated copper using a heated hydraulic press (50 seconds, 300°C, 4000 psi) to form a completed silicon composite electrode. The silicon-carbon composite electrode was inspected and analyzed.
[0151] Fig. 30a is a scanning electron microscope focused ion beam (SEM-FIB) image of a cross- section of an exemplary silicon-carbon composite material prepared from untreated silicon particles. Fig. 30b is a SEM-FIB image of a cross-section of an exemplary silicon-carbon composite material prepared from silane-treated silicon particles. The composite material made from silane-treated silicon had less porosity in the silicon-carbon interface region compared to the composite material made from untreated silicon.
[0152] In another example, silicon was added to a 2.5% solution of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane in N-methyl-2-pyrrolidone and milled with a zirconia medium for 6 hours. The resulting slurry was combined with graphite and a polyamic acid resin and coated onto a PET substrate. According to the process described above, the membrane was converted into a silicon-carbon composite electrode.
[0153] The silicon-carbon composite electrode was assembled into a lithium-ion cell comprising a cathode, a separator, and an electrolyte solution. The cathode consisted of a 15 µm aluminum foil coated with a 23 mg / cm², 3.02 g / cc membrane containing 95% NCM622, 2.5% conductive carbon additive, and 2.5% PVdF. The separator was a 16 µm porous polypropylene membrane coated with a 3.5 µm thick membrane composed of a mixture of PVdF and PMMA. The electrolyte solution contained 1.2 M LiPF6 in an organic carbonate. The nominal capacity of the cell design is 710 mAh. The cell was tested using a constant current / constant voltage charge profile and a constant current discharge profile. The upper voltage limit was 4.1 V, and the lower voltage limit was 2.75 V. The current was 1.42A during the charging phase, with a current limit of 0.035A during the constant voltage phase, and 0.35A during the discharging phase. Characterization cycles were performed every 50 cycles with a charging current of 0.35A and a discharging current of 0.14A.
[0154] Figure 31 shows a graph of capacity retention versus number of cycles for a whole cell containing silane-treated silicon particles versus a whole cell containing untreated silicon particles. The results for whole cells prepared with silane-treated silicon treated by water treatment and rotary evaporation process treatment are labeled "Silan-treated Si". The results for whole cells prepared with other silane treatments (e.g., by adding an organosilane to the slurry) are labeled "Silan Direct Addition". Two different organosilane (N-(2-aminoethyl)-3-aminopropyltrimethoxysilane) treatment conditions provided improved capacity retention for untreated silicon tested in whole cells for NCM622 at 4.1 V to 2.75 V.
[0155] Figure 32 shows a graph of capacity retention versus number of cycles for a whole cell containing silane-treated silicon particles versus a whole cell containing untreated silicon particles in a subsequent attempt (using the method of adding organosilane to the slurry). The results confirmed the performance improvement of organosilane-treated silicon under slightly modified test conditions (using a 4.2V upper voltage cutoff instead of 4.1V, and characterization cycles every 100 cycles).
[0156] Various embodiments have been described above. Although the invention has been described with reference to these specific embodiments, the description is for illustrative purposes only and is not intended to limit the invention. Various modifications and applications may come to mind to those skilled in the art without departing from the true spirit and scope of the invention as defined in the appended claims.
Claims
Claim 1 A method for forming a composite film, comprising the steps of: providing a mixture comprising a precursor and silane-treated silicon particles; and pyrolyzing the mixture to convert the precursor into one or more carbon phases to form a composite film having silicon particles distributed across the composite film, wherein the silane treatment of the silicon particles is performed in a sealed container under atmospheric pressure, and the interface region defined between the silicon particles and the carbon phase has a porosity of 30% or less. Claim 2 A method for forming a composite film according to claim 1, wherein the silane-treated silicon particles comprise silicon particles treated with one or more organosilanes. Claim 3 A method for forming a composite film according to paragraph 2, wherein the silane-treated silicon particles comprise a silicon oxide surface that reacts with one or more organosilanes. Claim 4 A method for forming a composite film according to claim 2, wherein the one or more organosilanes comprise one or more silanols, silyl ethers, silyl chlorides, dialkylaminosilanes, silyl hydrides, or cyclic azasilanes. Claim 5 A method for forming a composite film according to claim 4, wherein the one or more organosilanes comprise one or more aminoalkyl functional groups. Claim 6 A method for forming a composite film according to claim 5, wherein one or more organosilanes comprise 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, or 2,2-dimethoxy-1,6-diaza-2-silacyclooctane. Claim 7 In paragraph 5, a method for forming a composite film, wherein the precursor comprises polyimide. Claim 8 A method for forming a composite film according to claim 4, wherein one or more organosilanes comprise an epoxide linker. Claim 9 A method for forming a composite film according to claim 8, wherein the epoxide linker comprises 5,6-epoxyhexyltriethoxysilane. Claim 10 A method for forming a composite film according to claim 8, wherein the precursor comprises a phenol resin. Claim 11 A method for forming a composite film according to claim 4, wherein one or more organosilanes comprise an aromatic functional group. Claim 12 A method for forming a composite film according to claim 11, wherein at least one organosilane comprises benzyltriethoxysilane. Claim 13 A method for forming a composite film according to claim 11, wherein the precursor comprises a polycyclic aromatic hydrocarbon. Claim 14 A method for forming a composite material film according to claim 4, wherein one or more organosilanes include dodecylsilane. Claim 15 A method for forming a composite film according to claim 4, wherein one or more organosilanes comprise (N,N-dimethylamino)trimethylsilane. Claim 16 A method for forming a composite film according to paragraph 2, wherein the silicon particles are suspended in a liquid containing one or more organosilanes. Claim 17 A method for forming a composite film in which the silicon particles are exposed to one or more organosilane vapors in paragraph 2. Claim 18 In paragraph 2, a method for forming a composite film, wherein the mixture comprises one or more organosilanes. Claim 19 A method for forming a composite material film according to claim 1, wherein the composite material film comprises 50% by weight to 99% by weight of the silicon particles. Claim 20 A method for forming a composite material film according to claim 1, wherein the composite material film is electrochemically active. Claim 21 A method for forming a composite film according to claim 1, wherein at least one of the one or more types of carbon phases is a continuous phase that maintains the composite film. Claim 22 A method for forming a battery electrode comprising: providing a mixture comprising a precursor and silane-treated silicon particles; pyrolyzing the mixture to convert the precursor into one or more carbon phases to form a composite film having silicon particles distributed across the composite film; and forming an electrode comprising the composite film, wherein the silane treatment of the silicon particles is performed in a sealed container under atmospheric pressure, and the interface region defined between the silicon particles and the carbon phase has a porosity of 30% or less. Claim 23 A method for forming a battery electrode, wherein the electrode is an anode, in paragraph 22.
